The Quiet Voices : Southern Rabbis and Black Civil Rights, 1880s to 1990s - Bauman, Mark K. (Book collections on Project MUSE., 2013)
These wide-ranging essays reveal the various roles played by southern rabbis in the struggle for black civil rights since ReconstructionThe study of black-Jewish relations has become a hotbed of controversy, especially with regard to the role played by Jewish leaders during the Civil Rights movement. Did these leaders play a pivotal role, or did many of them, especially in the South, succumb to societal pressure and strive to be accepted rather than risk being persecuted? If some of these leaders did choose a quieter path, were their reasons valid? And were their methods.